2014
DOI: 10.1074/jbc.m114.587865
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor of Activated T Cells Regulates the Expression of Interleukin-4 in Th2 Cells in an All-or-none Fashion

Abstract: Background: Not every T helper type 2 (Th2) lymphocyte imprinted to express interleukin-4 (IL-4) does so when activated.Results: Preventing nuclear translocation of the nuclear factor of activated T cells (NFAT) reduces the number of Th2 lymphocytes reexpressing IL-4.Conclusion: NFAT is the limiting factor determining digital IL-4 expression in Th2 lymphocytes.Significance: This might help us to understand the regulation of immunopathology in allergy and asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…2D and E). We did not observe significant binding to confirmed STAT6-binding sites in humans [44] or mice [45] (Supplemental Fig. 2D and E).…”
Section: Il-12 Causes Stat4-dependent Mll1 Expressionmentioning
confidence: 77%
“…2D and E). We did not observe significant binding to confirmed STAT6-binding sites in humans [44] or mice [45] (Supplemental Fig. 2D and E).…”
Section: Il-12 Causes Stat4-dependent Mll1 Expressionmentioning
confidence: 77%
“…Although heterogeneity of Th2 cells can be a result of differential epigenetic status of each cytokine allele 215, 216 , the actual cytokine production in a given cell upon a single round of stimulation may be a stochastic event 217 . Heterogeneous activation of transcription factors such as NFAT or differential assembly of functional transcription factor complex needed for inducing cytokine production may be one of the main explanations 217, 218 . Thus, IL-4- and/or IL-13-non-producing cells identified after stimulation at one time may express these cytokines in response to another round of stimulation.…”
Section: Induction Of Il-4 and Il-13 Expression By Th2 Cellsmentioning
confidence: 99%
“…However, a recent investigation showed that a single peptide/MHC complex can initiate the response of CD4 + T cell and that additional pMHC molecules do not increase the secretion of effector cytokines (such as IL-2 or TNFa), demonstrating an ‘all or none’ type of response [137]. The follow-up of the secretion of Th2 cytokine, IL-4, strictly requires the presence of NFAT in the nucleus and analogue differences in TCR triggering are converted into digital outcome of NFAT nuclear translocation [138]. It is noteworthy that activation of NFAT itself is a digital process because it requires the complete—highly cooperative—dephosphorylation by CaN of 13 serine residues, which hide the nuclear localization signal segment inside the protein [139].…”
Section: Analogue and Digital Signalling In T Lymphocytesmentioning
confidence: 99%
“…At the same time, MAPK responds gradually to stimulation of Jurkat cells with SDF-1, reflecting plasticity in the reaction of T cells to chemokine gradients [141]. In addition, the activation of NFκB showed analogue [138] and digital [142] modes after gradual T cell stimulation.…”
Section: Analogue and Digital Signalling In T Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation